DEVELOPING A SUPPLEMENTARY ENGLISH READING MATERIAL USING TASK-BASED LANGUAGE TEACHING FOR THE EIGHT GRADE STUDENTS - Zakiyah Aulia Putri; Muhammad Luthfi Abdillah; Moh. Hilman Fikri; Wahyu Sudrajad (EDUCATUM: Scientific Journal of Education, 2024)
This study aims to develop English reading materials based on a task-based language teaching approach for the eighth-grade students of SMP Muallimat Gresik. This study was conducted to solve the problem faced by the eighth-grade students of SMP Muallimat Gresik in reading interest and how to develop reading materials for the eighth-grade students of SMP Muallimat Gresik. This research uses a research method in the form of a research and development method R&D, this research and development design includes several stages. Need analysis, studied theories related to reading problems, the result of the needs analysis was developed into a textbook, and expert validation was conducted to determine the quality of the product again until the writer felt confident that the product could be published perfectly. The final product of this study is the textbook of Reading material which focuses on increasing students’ reading skills; this reading material is developed based on the students' needs and students’ interests.